PTEN mutations as predictive marker for the high-grade endometrial cancer development in slovak women - Gbelcová, Helena; Gergely, Lajos; Šišovský, Vladimír; Straka, Ľubomír; Böhmer, Daniel; Pastoráková, Andrea; Sušienková, K; Repiská, Vanda; Korbeľ, Miroslav; Danihel, Ľudovít; Priščáková, Petra (Physiological research, 2022)
Endometrial carcinoma (ECa) is one of the most common neoplasia of the female genital tract. The phosphatase and tensin (PTEN) homolog is the most frequently mutated tumor suppressor gene in endometrial carcinoma. PTEN encodes a phosphatase, a key regulatory enzyme involved in a signal transduction pathway that regulates cell growth, migration and apoptosis. The study evaluates an association between the morphological appearance of endometrial hyperplasia and ECa, and the presence of PTEN variations, PTEN protein ́s level and intracellular localization. A total of 67 archived formalin-fixed and paraffin-embedded human biopsy tissue specimens with normal proliferative and secretory endometrium, endometrial hyperplasia without atypia and endometrial atypical hyperplasia, endometrioid the grade G1 and G3 and serous subtype of ECa were evaluated by sequencing for the presence of mutations in coding regions of PTEN gene of endometrial epithelial cells. The PTEN gene expression and intercellular localization of PTEN protein were evaluated immunohistochemically by immunoreactive score (IRS). PTEN mutation spectrum in endometrial carcinoma was identified for Slovak population. 28 non-silent mutations were identified in PTEN, twelve of them were novel, not annotated in Catalogue of Somatic Mutations in Cancer. Higher frequency of PTEN mutations was observed in serous carcinoma compared to global average. No correlation was observed between samples ́ IRS, PTEN cellular localization and identified mutations. PTEN sequencing can be beneficial for patients considering prognosis of disease and sensitivity to treatment.
Keywords: nádory endometria; mutace; Endometrium; PTEN Phosphohydrolase; endometrium; Slovakia; Endometrial Neoplasms; hyperplazie endometria; lidé; Slovenská republika; Female; fosfohydroláza PTEN; Mutation; ženské pohlaví; Endometrial Hyperplasia; Humans